2011
DOI: 10.4103/0972-124x.82270
|View full text |Cite
|
Sign up to set email alerts
|

Accidental identification of accessory mental nerve and foramen during implant surgery

Abstract: The accessory mental nerve and the corresponding foramen are not a very common occurrence. In the current case report, we present the notice of an accessory mental nerve in the mandibular molar area during implant placement. The case was managed well without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
(13 reference statements)
0
12
0
1
Order By: Relevance
“…Arx et al (2014) described four cases of apical surgery in which an AMN was present. Kulkarni et al (2011) reported a case in which an AMN was found during implant placement in the buccal aspect of the alveolar bone. Three patients had no symptoms of paresthesia after surgery.…”
Section: Clinical Casesmentioning
confidence: 99%
“…Arx et al (2014) described four cases of apical surgery in which an AMN was present. Kulkarni et al (2011) reported a case in which an AMN was found during implant placement in the buccal aspect of the alveolar bone. Three patients had no symptoms of paresthesia after surgery.…”
Section: Clinical Casesmentioning
confidence: 99%
“…Los hallazgos accidentales de FMA en procedimientos clínicos han sido documentados (Kulkarni et al;Hanratty, 2012 y Mamatha et al), obligando a modificar la planificación de la cirugía para evitar eventuales complicaciones por lesión de nervios. Por lo anterior, el apoyo con imagen 3D en la visualización de FMA, es una herramienta útil en el manejo de estas situaciones.…”
Section: Discussionunclassified
“…In a study which was done on 525 dry mandibles, Gerhenson et al, reported that 4.3% of the mandibles had double mental foramens, 0.7% had triple mental foramina and that one mandible had 4 mental foramina on one side [6]. Injuries to any of the nerves during surgical procedures in this area can cause anaesthesia or paraesthaesia [7].…”
Section: Discussionmentioning
confidence: 99%